Hepatic Epithelioid Angiomyolipoma and 18F-FDG PET/CT. (June 2018) - Zhang, Yiqiu; Li, Beilei; Hou, Jun; Yu, Haojun; Shi, Hongcheng
Abstract : Abstract: Hepatic epithelioid angiomyolipoma (AML) is rare. Although generally epithelioid AML shows benign biological behavior, it can occasionally have malignant potential. In this study, we report a case of 2 hepatic epithelioid AMLs with different 18 F-FDG uptake; one is intensely FDG avid, and the other is non–FDG avid.